Engineering Analysis and Recognition of Nigerian English: An Insight into Low Resource Languages. (2014) - Amuda, Sulyman A. Y.; Boril, Hynek; Sangwan, Abhijeet; Hansen, John H. L.; Ibiyemi, Tunji S.
No abstract available